Character Education In The Digital Era Overcoming Hate Speech Through Social Media Ethics Awareness Among Students - Muhammad Caesar Akbar; Syifa Armiyanti (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
This study aims to explore the role of character education in building digital ethics awareness among students of Medan Aviation Polytechnic as an effort to address the issue of hate speech on social media. Using a qualitative descriptive approach, this research delves into the factors influencing students' digital behavior, including legal literacy, self-control, and moral education. The results indicate that 95% of students have witnessed hate speech on social media, and 40% of them admit to having been involved in such practices. However, only 25% of students have a deep understanding of digital legal regulations. Character education proves to be effective in enhancing emotional intelligence, empathy, and critical thinking skills among students, thus contributing to the reduction of hate speech intensity. This study recommends the integration of digital ethics into the curriculum, the development of continuous training programs, and multidimensional collaboration between educational institutions, families, and communities to create an inclusive and responsible digital culture.